Security and rescue research of the burial ground "Brotherly 1st barrows"on the territory of the Chechen Republic in 2018 - Malasev, Vladimir Ur'evic; Magomedov, Rabadan Gadzievic; Dzucev, Feliks Safarbekovic; Mamaev, Hamid Magomedovic; Krivoseev, Mihail Vasil'evic (History, Archeology and Ethnography of the Caucasus, 2018)
In June-October 2018 Terek complex archaeological expedition ("scientific and production center "Dagestan archaeological service"), Caucasian expedition (Institute of archeology RAS) and Chechen expedition (Institute of humanitarian research of the Academy of Sciences of the CR), bringing together experts from Vladikavkaz, Volgograd, Grozny, Makhachkala, Moscow, Simferopol, etc., at the expense of PJSC "Gazprom" / LLC "Gazprominvest" (St. Petersburg) and LLC "Kirus" (Grozny), we conducted security and rescue research in the territory of the super – terrechny district of the Chechen Republic in the area of construction of the main gas pipeline "Mozdok-Grozny". Of greatest interest are the materials of the burial ground "Fraternal 1st mounds" (162 burial complex), Dating from the III-IV centuries ad and is the necropolis of the Fraternal 1st settlement, Dating from the early stage of the Alanian culture. The named necropolis occupies an approximate territory of 6.5 x 3.5-2 km. In the present article the General review of the investigated burials of the named barrow burial ground which many embankments are destroyed as a result of economic activity is presented. The result of this work was excavated barrow 162 and beskarkasnyh funeral complex. The vast majority of burials were made in catacombs of type I (the long axis of the chamber is perpendicular to the long axis of the entrance pit). The investigated sample of burials makes it possible to consider this monument a reference to the territory of the Middle Primerica at the specified time. The population, which left the burial grounds type "Fraternal 1st barrows", participated in the cultural and historical processes in the territory West of the Caspian sea, where their presence is recorded in the Terek-Sulak interfluve in the second half of the III century ad, and from the middle of IV century BC, in southern Dagestan, where, according to information from written sources, localized "Country land".